1987
DOI: 10.1055/s-2008-1054088
|View full text |Cite
|
Sign up to set email alerts
|

Einfluß lokal applizierter Kortikoide auf die Morphologie peripherer Nerven nach Neurotmesis und mikrochirurgischer Naht*

Abstract: The present work deals with the morphology of cut peripheral nerves anastomosed by primary microsurgical suture. The important question was whether the well-known anti-inflammatory, anti-exudative and fibroblast-inhibiting effects of locally applied glucocorticoids can influence the morphology of degenerating and regenerating peripheral nerves. After cutting the saphenous nerve of the rabbit and prior to its microsurgical suture the synthetic crystalline glucocorticoids methylprednisolone, prednisolone and dex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…Higher numbers of regenerating axons than with vehicle injection were also found if cortisol was applied alone. This is in contrast to the findings of Becker et al [6] and several other studies, in which no enhancement of regeneration of damaged axons after the application of corticoids could be found [9,26]. On the other hand, better regeneration of cut nerves was also found [29].…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Higher numbers of regenerating axons than with vehicle injection were also found if cortisol was applied alone. This is in contrast to the findings of Becker et al [6] and several other studies, in which no enhancement of regeneration of damaged axons after the application of corticoids could be found [9,26]. On the other hand, better regeneration of cut nerves was also found [29].…”
Section: Discussioncontrasting
confidence: 86%
“…However, this procedure may lead to wrong conclusions. Becker et al cut and re-sutured the nervus saphenus of rabbits and compared the neuroanatomical changes with and without local application of glucocorticoids [6]. They found that Wallerian degeneration, i.e.…”
Section: Discussionmentioning
confidence: 98%
“…The most commonly used drugs in peripheral nerve injuries are steroids. Steroids demonstrate an antiin ammatory action by inhibiting the phospholipase A2, suppressing the macrophage inhibition factor, stabilizing the lysosomal and other membranes, granulocytes (Graham et al 1973 Becker et al reported that local steroid applications reduce the number of broblasts and scar tissue formations in peripheral nerve injuries (Becker et al 1987). In addition, in the same study, they reported that steroids prevented the neuroma formation with these effects and stimulated myelin sheath production through the activation of Schwann cells.…”
Section: Discussionmentioning
confidence: 99%